Transcendental Pedagogical Awareness in Digital Learning Transformation: A Phenomenological Study of Islamic Education Teachers in Frontier Areas of East Kalimantan - Dody Wisono; Syamsul Arifin; M. Nurul Humaidi; Syamsurizal Yazid (Al Qodiri : Jurnal Pendidikan, Sosial dan Keagamaan, 2026)
Digital transformation in education has reshaped teaching and learning practices, encouraging Islamic Education teachers to reconsider the ways in which technology can support educational goals and moral development. While previous studies have predominantly focused on digital competence and technology integration, the spiritual and reflective dimensions underlying teachers’ responses to educational change remain insufficiently explored. This study investigates the transcendental pedagogical awareness of Islamic Education teachers in frontier areas of East Kalimantan during the process of digital learning transformation. Employing a qualitative approach grounded in transcendental phenomenology, data were collected through in-depth interviews, observations, and documentation involving teachers from senior high schools and vocational schools in Berau Regency. The analysis identified four interconnected dimensions of transcendental pedagogical awareness: muhasabah as the foundation of innovative awareness, technology as a value-oriented pedagogical medium, the emergence of teachers as micro digital content creators, and pedagogical resilience in addressing frontier educational challenges. The findings indicate that meaningful digital transformation extends beyond technological proficiency and is sustained by the integration of spiritual reflection, pedagogical commitment, and contextual adaptation. This study proposes the concept of Transcendental Pedagogical Awareness as a framework for understanding value-based digital transformation in Islamic education.